Longitudinal bidirectional relations between parental phubbing and adolescents’ life satisfaction: The roles of problematic social network use and personality - Xiaoyan Zhou; Fangfang Tian; Xingchao Wang; Xinyi Chen; Jiping Yang; Xueqi Zeng (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2025)
Parental phubbing, as a new negative factor for adolescents’ healthy and positive development, has been noticed by scholars. The current study explored the longitudinal association between parental phubbing and adolescents’ life satisfaction across three years, taking into account adolescents’ problematic social network use as a potential mediator and Big Five personality traits as moderators of the associations. This study involved 2,407 Chinese adolescents (Mage = 12.75, SD = 0.58 at baseline, range = 11–16) by questionnaire. The involved students were recruited from 48 classrooms across 7 different schools. Structural Equation Modeling (SEM) was used to fit our cross‐lagged panel model across three waves of data. The results showed that the relation between parental phubbing and adolescents’ life satisfaction is negative and bidirectional. Problematic social network use mediated the relation between parental phubbing and adolescents’ life satisfaction. Agreeableness moderated the relations among parental phubbing, problematic social network use, and adolescents’ life satisfaction. Specifically, the negative bidirectional relations between parental phubbing and adolescents’ life satisfaction were more robust for adolescents with low agreeableness than those with high agreeableness. Compared to adolescents with low agreeableness, adolescents who with high agreeableness experienced high parental phubbing at previous time points were more likely to have problematic social network use at subsequent time points. The present study indicates that perceived high parental phubbing can be both a precursor to and an outcome of adolescents’ low life satisfaction, serving to maintain a vicious cycle that compounds negative effects on student mental health. Further, results demonstrate how problematic social network use and personality can affect this cycle.